2020
DOI: 10.2320/matertrans.mt-m2019351
|View full text |Cite
|
Sign up to set email alerts
|

Changes in States of Carbon and Mechanical Properties with Aging at 50°C after Quenching in Low Carbon Steel

Abstract: The changes in the states of carbon (C) together with hardness and the tensile properties of low C steel (0.045C0.34Mn in mass%) quenched from 710°C and aged at 50°C were investigated as a function of aging time using TEM and atom probe tomography. Vickers hardness increases at about 1.1 © 10 4 s, exhibits significant increase at 5.8 © 10 4 s (16 h) and maintains peak hardness untill 8.6 © 10 5 s (10 d) followed by a decrease after further aging time. At the start of peak aging, C clusters form with an irregul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Such observations have also revealed that the carbon clusters are distributed at intervals of approximately 20 nm in the two-dimensional view of APT data and at intervals of approximately 30 nm if a square lattice distribution is assumed using the number density and cluster diameter. 1) Given the observations reported thus far, 1,46) this steel material is understood to exhibit peak aging by transitioning from the homogenous solid-solution state of the solution-treated material to carbon clusters during aging; it subsequently exhibits age-softening by changing its morphology to ¾-carbides, etc. However, why carbon clusters exhibit maximum hardness remains unclear.…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations
“…Such observations have also revealed that the carbon clusters are distributed at intervals of approximately 20 nm in the two-dimensional view of APT data and at intervals of approximately 30 nm if a square lattice distribution is assumed using the number density and cluster diameter. 1) Given the observations reported thus far, 1,46) this steel material is understood to exhibit peak aging by transitioning from the homogenous solid-solution state of the solution-treated material to carbon clusters during aging; it subsequently exhibits age-softening by changing its morphology to ¾-carbides, etc. However, why carbon clusters exhibit maximum hardness remains unclear.…”
Section: Introductionmentioning
confidence: 91%
“…The carbon clusters characterized by APT have a carbon concentration of 1³2 at% and a diameter of approximately 10 nm, and the distance between the centers of the clusters is approximately 20³30 nm. 1) In the present paper, analysis models are constructed on the basis of actual APT measurements and the shape of the carbon cluster is assumed to be a sphere with diameter D. The carbon cluster is modeled by randomly arranging N carbon atoms at stable interstitial sites of the carbons in a spherical range of D diameters in ¡-Fe. The number N of carbon atoms is set to 630³640, referring to the value (700) calculated from the measured carbon concentration of APT.…”
Section: Modeling Of a Carbon Clustermentioning
confidence: 99%
See 2 more Smart Citations
“…11 (2020) pp. 21392148) 5,13) To investigate the reason why low-carbon steels with carbon-clusters shows the maximum strength during lowtemperature aging, 34) interactions between an edge dislocation and carbon clusters are performed through molecular dynamics (MD) simulations. 35,36) Carbon clusters are modeled based on atom probe tomography (APT) observations.…”
Section: "A Mechanism Of Carbon-cluster Strengtheningmentioning
confidence: 99%